2022
DOI: 10.1371/journal.pone.0274884
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer management in Zimbabwe (2019–2020)

Abstract: Background Globally, cervical cancer is the fourth most commonly diagnosed cancer amongst women, and it is especially common in low- and middle-income countries (LMICs). The aim of the study was to determine the current patterns and characteristics of CC management in Zimbabwe in the HIV pandemic era, including the knowledge, attitude and practice of patience. Methods The study was a mixed method which incorporated a cross-sectional survey of 408 CC patients which was conducted from October 2019 to September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
5
9
0
Order By: Relevance
“…The adverse effects of the COVID − 19 pandemic on the socio-economic status and patient's well-being may have additionally contributed to the low treatment adherence rates. The present ndings relate to those published by authors in Zimbabwe's Parirenyatwa hospital where radiotherapy uptake was reported in about 86% of the patients, with only 38% administered with chemotherapy [13]. In both settings, similar health system constraints are reported [13,14,24].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The adverse effects of the COVID − 19 pandemic on the socio-economic status and patient's well-being may have additionally contributed to the low treatment adherence rates. The present ndings relate to those published by authors in Zimbabwe's Parirenyatwa hospital where radiotherapy uptake was reported in about 86% of the patients, with only 38% administered with chemotherapy [13]. In both settings, similar health system constraints are reported [13,14,24].…”
Section: Discussionsupporting
confidence: 83%
“…Chemoradiation treatment non-compliance has been reported in studies done previously in low-and middleincome countries [13,15,16], however, most of these studies were done in populations outside Uganda. In the present study, the rate of compliance to chemoradiation treatment among cervical cancer patients at Uganda Cancer Institute was determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations